Conclusion and recommendations - SANCHEZ, Marco Antonio ORTIZ (A+BE | Architecture and the Built Environment, 2019)
This research provided insights into the comfort and energy-consuming behaviours of home occupants and into grouping these home occupants based on their individual differences. This was achieved by using a human-centered approach to an engineering challenge, by assuming comfort as a holistic experience of the home environment, and by treating the ‘occupant-environment’ interactions as a dynamic system. Such an approach drew methods typically used in design and ethnographic research, by gathering both qualitative and quantitative data from both the occupant and the building. The occupant data was collected quantitatively with the use of a questionnaire (self-reported) and qualitatively with interviews (procedural knowledge) and finally with generative techniques (interpretive knowledge). In such a way, different types of occupant knowledge were elicited and collected. The building data was gathered with checklists, monitoring, and energy readings. With the questionnaire data and a clustering technique -the TwoStep cluster analysis- five distinct types of occupant, or archetypes, were discovered and they were progressively enhanced and substantiated with the interview and generative techniques data. Additionally, data of building characteristics, indoor environmental factors, and actual energy consumption completed the details of the archetypes. The following paragraphs provide the conclusion and recommendations drawn from this research. First each of the key questions are answered followed by the answer to the main research question; in which the final description of the archetypes is presented. This is followed by the strengths and limitations of this work and recommendations for the future process. Then for each archetype, environmental design parameters are presented. This finishes with recommendations for future research and the implications of this work.